THE ROLE OF CONTEXT IN TRANSLATION OF AXIOLOGICAL LEXEMES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This paper shows how to translate axiological lexemes between English and Uzbek. Good translation starts with context: the narrow context (phrase or sentence), the wide context (whole text), and real-world factors (culture, setting, genre). We review equivalence types (full, partial, intersecting, complicated) and explain why direct, word-for-word choices often fail. We propose four practical methods—modification, form/function description, descriptive translation, and comparison—to keep the original evaluation (praise, blame, irony, taboo) in lexemes.